First Record of an Established Population of Triatoma sanguisuga (Hemiptera: Reduviidae) in Richardson County, Nebraska. Issue 6 (20th July 2021) - Nielsen, David H; Koch, Kyle; Roachell, Walter; Delgado, Bernardo; Bast, Joshua
Abstract: In 2017, a single adult Triatoma sanguisuga (LeConte) (Hemiptera: Reduviidae) was identified from Indian Cave State Park in Nemaha County, NE. The following summer, a single adult specimen was found in a 4-H insect collection at the Nebraska State Fair from Richardson County. A subsequent investigation found that these were collected from a residence in Richardson County and three more adults were collected in 2019. In 2020, the latter three kissing bugs were submitted to Public Health Command-Central's DoD Food Analysis and Diagnostic Laboratory (DOD FADL) for confirmatory species identification and diagnostic testing for Trypanosoma cruzi, the causative agent of Chagas disease. One specimen tested positive for T. cruzi using a real-time dual-target PCR screen followed by confirmatory dual-target traditional PCR. Based on these findings, a survey plan was developed for Richardson and surrounding counties in southeast Nebraska. In July of 2020, two adult and seven nymphs (multiple instars) of T. sanguisuga were collected in Richardson County, one of which tested positive for T. cruzi . This is the first record of an established population of T. sanguisuga and T. cruzi -infected kissing bugs in Nebraska.